Inovasi Pemasaran Dalam Mendorong Pertumbuhan Usaha Mikro Di Desa Sentol Pamekasan - Syaiful Syaiful; Fredy Yunanto; Mohammad Rudiyanto; Sholeh Rachmatullah; Ria Kasanova (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
The "Marketing Innovation in Encouraging Micro Business Growth in Sentol Pamekasan Village" Community Service Program (PKM) aims to increase the competitiveness and economic well-being of microbusinesses in rural Indonesia. Microenterprises hold significant value in both local and national economies. In an era of dynamic economic expansion and continuous social transformation, the growth and progress of microenterprises are of the utmost importance. The potential for micro businesses in Desa Sentol, Pamekasan, is substantial; nonetheless, proprietors of such enterprises encounter several obstacles, such as restricted market entry, intensifying competition, and a dearth of comprehension about efficacious marketing tactics. PKM places emphasis on marketing innovation as a potential resolution to this issue. The outcomes of this PKM initiative demonstrate a substantial positive influence. A 20 to 30 percent increase in the income and profitability of microenterprises contributes to enhanced economic well-being for microbusiness proprietors and the Desa Sentol community at large. Moreover, new marketing methods expand market penetration, hence generating more prospects for business expansion. Additionally, the results indicate that proprietors of microbusinesses in Desa Sentol have assimilated sustainable practices and a commitment to innovative marketing strategies. The significance of strengthening collaboration between microbusiness proprietors, local governments, and other pertinent stakeholders, as well as continuing to utilize marketing innovations, is illuminated by these findings. Ongoing support is provided through advanced training and technical mentoring. Future recommendations encompass the implementation of advanced training initiatives, continuous mentorship programs, enhanced cooperation channels, and the expansion of the range of products and services offered. By fostering ongoing assistance and expanding inventive capacity, Desa Sentol possesses substantial potential to emerge as a paradigm of achievement in the rural micro-enterprise sector of Indonesia. Additionally, this PKM program may serve as a model for other places confronting comparable obstacles.